A biofidelic computational model of the female pelvic system to understand effect of bladder fill and progressive vaginal tissue stiffening due to prolapse on anterior vaginal wall. (2nd March 2016) - Chanda, Arnab; Unnikrishnan, Vinu; Richter, Holly E.; Lockhart, Mark E.
Summary: Treatment of anterior vaginal prolapse (AVP), suffered by over 500, 000 women in the USA, is a challenge in urogynecology because of the poorly understood mechanics of AVP. Recently, computational modeling combined with finite element method has been used to model AVP through the study of pelvic floor muscle and connective tissue impairments on the anterior vaginal wall (AVW). Also, the effects of pelvic organ displacements on the AVW were studied numerically. In our current work, an MRI‐based full‐scale biofidelic computational model of the female pelvic system composed of the urinary bladder, vaginal canal, and the uterus was developed, and a novel finite element method framework was employed to simulate vaginal tissue stiffening and also bladder filling due to expansion for the first time. A mesh convergence study was conducted to choose a computationally efficient mesh, and a non‐linear hyperelastic Yeoh's material model was adopted for the study. The AVW displacements, mechanical stresses, and strains were estimated at varying degrees of bladder fills and vaginal tissue stiffening. Both bladder filling and vaginal stiffening were found to increase the stress concentration on the AVW with varying trends, which have been discussed in detail in the paper. To our knowledge, this study is the first to estimate the individual and combined effects of bladder filling and vaginal tissue stiffening due to prolapse on the AVW. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The individual and combined effects of vaginal tissue stiffening due to prolapse, and bladder filling with expansion, on the anterior vaginal wall (AVW) was studied for the first time. An MRI‐based computationally efficient female pelvic system model was developed, and the stresses, strains, and displacements at the anterior vaginal wall were quantified. Clinically relevant trends were investigated, which would provide important guidelines to the urogynecological surgeons for planning prolapse‐based surgeries and mitigation strategies in the future.